Implementation of Legal Sanctions Against Criminal Actions of Corruption (Study of Decision Number 8/PID.SUS-TPK/2020/PN JKT.PST) - Bambang Asmoyo; Adi Sujatno; Dadang Suherli Saputra (LEGAL BRIEF, 2022)
The crime of corruption is categorized as an extraordinary crime because the impact is extraordinary, which has occurred systematically and widely, not only harming state finances, disturbing the stability and security of society, weakening democratic values, ethics, justice and legal certainty, has also violated the social and economic rights of the community at large. The crime of corruption is included in the category of a very large crime and is very detrimental to the nation and state in one region. Therefore, the corruption law and the judicial system are very different, and there is a special institution that plays an important role in eradicating corruption. The research method used is normative juridical, namely library law research which is carried out by examining library materials or secondary data. The results of the research include that regarding the regulation of criminal acts of corruption contained in Law no. 31 of 1999 concerning the Crime of Corruption, which took effect on August 16, 1999 which was later amended by Law no. 20 of 2001 concerning Amendments to Law no. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption.